2022
DOI: 10.15282/ijame.13.3.2016.8.0298
|View full text |Cite
|
Sign up to set email alerts
|

Damaging fatigue cycles determination for random service loadings using mixed Weibull analysis

Abstract: This paper investigates the fatigue damage behaviour of random service loading histories and suggests a criterion to determine fatigue damaging cycles by using probability values. The rainflow strain range distribution is often used in fatigue damage prediction. The existence of very small amplitude of cycles that do not significantly contribute to damage makes the prediction process unnecessarily complex. Therefore, a criterion to determine the size of damaging cycles that contribute significantly to total da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Fatigue occurs when a material is subjected to cyclical loads and is an irreversible and inevitable phenomenon in the process of use. Several fatigue life estimation models based on the Weibull statistical distribution, modified Wöhler curve and specified endurance function have been reviewed for applications in steel alloys [17,18]. An integrated continuum mechanics model with a genetic algorithm was examined for the multiaxial fatigue response of steel samples [19,20,21,22,23].…”
Section: Fig 3 Views Of Rope Cross-sections (Top) and Surfaces (Botto...mentioning
confidence: 99%
“…Fatigue occurs when a material is subjected to cyclical loads and is an irreversible and inevitable phenomenon in the process of use. Several fatigue life estimation models based on the Weibull statistical distribution, modified Wöhler curve and specified endurance function have been reviewed for applications in steel alloys [17,18]. An integrated continuum mechanics model with a genetic algorithm was examined for the multiaxial fatigue response of steel samples [19,20,21,22,23].…”
Section: Fig 3 Views Of Rope Cross-sections (Top) and Surfaces (Botto...mentioning
confidence: 99%
“…In the known literature, the Wöhler curve and the strength function have been defined for applications in steel alloys. An integrated continuum mechanics model with a genetic algorithm was investigated for the multi-axis fatigue response of steel samples [20][21][22][23][24][25][26].…”
Section: Probability Of Occurrence Of Wire Cracks In the Working Rope...mentioning
confidence: 99%
“…Zhao et al [9] have reported the fatigue-life prediction of wire ropes using the Wöhler curve, while Kamal & Rahman [11] make some modifications to the curve to predict the fatigue-life of steel alloys. Other than that, the fatigue life prediction of steel alloys has also been done by Mahmud et al [12] by utilizing the Weibull statistical distribution approach. These conventional methods used phenomenological approach that is based on the mean load over the net section area of the wire ropes, without taking into consideration the failure of individual wires in the strand under fatigue stressing.…”
Section: Introductionmentioning
confidence: 99%